Why ethics?: signs of responsibilities - Gibbs, Robert (Princeton University Press, 2000)
Robert Gibbs presents here an ambitious new theory of ethics. Drawing on a striking combination of intellectual traditions, including Jewish thought, continental philosophy, and American pragmatism, Gibbs argues that ethics is primarily concerned with responsibility and is not--as philosophers have often assumed--principally a matter of thinking about the right thing to do and acting in accordance with the abstract dictates of reason or will. More specifically, ethics is concerned with attending to others' questions and bearing responsibility for what they do.